Analisis Pengaruh Kompensasi, Keamanan Kerja Dan Beban Kerja Terhadap Keinginan Untuk Berpindah Melalui Komitmen Organisasional Sebagai Variabel Intervening (Studi Kasus Pada PT. Mitra Aneka Rezeki Kabupaten Kubu Raya) - Putra, Sulaiman Ratulaly (Universitas Tanjungpura, 2019)
This study aims to determine the significant effects of compensastion, job security, workload, organizational commitment on the desire to move at PT. Mitra Aneka Rezeki of Kubu Raya Regency. This research was conductted on casuall daily workers and laborers under employment conditions of PT. Mitra Aneka Rezeki with a total sample of 91 of people. The method of determining the sample uses the slovin formula technique. The data obtained by distributing questionaires were analyzed using validity, relaibility, and hyphotesis test. The result of hyphotesis show that compensation, job security and workload have significant results on organizational commitment; and compensation , job security and workload have significant results the desire to move through organizational commitment. The partical implication of this research is the finding for the management in terns of anticipating the workerswilling to move by paying attention ti the compensasion received, job security faced, excessive workload and low organizational commitment.Â Keywords: Compensation, Work Security, Workload, Organzational Commitment and Desire To Move.